Ability of biochar to facilitate anaerobic digestion is restricted to stressed surroundings. (20th November 2019) - Shao, Liming; Li, Shasha; Cai, Jiao; He, Pinjing; Lü, Fan
Abstract: Additives or external voltage are usually applied to promote methane production and organics degradation through the possible means of enhancing direct interspecies electron transfer (DIET), but their effectiveness and explanation are controversial. In this work, external voltage and additives (biochar and zeolite) were applied simultaneously and independently to laboratory-scale anaerobic reactors for further clues of DIET-enhancing mechanism. External voltage was indicated to impede methanogens early, and promote anaerobic process later. Boichar was discovered to benefit only stressed scenarios caused by external voltage or microbial inactivity, but express no significant influence on well-operating ones, which could be attributed to the finding that biochar enriched DIET-capable Methanosarcina and Methanosaeta which are sensitive to stress. Zeolite could not overcome external handicaps with only increase of microbial amounts and diversity but without selectivity. The BET specific areas of biochar (13.6 m 2 /g) and zeolite (15.1 m 2 /g) applied in this work are semblable, which excludes the discrepancy in adsorption of inhibitors between the biochar and zeolite. The electron donating capacities (EDC) of biochar and zeolite are, respectively, 0.17 and 0 mmol e − /g, while electron accepting capacities (EAC) are similar, revealing that EDC did great benefit to the promotion hence the enrichment of Methanosarcina and Methanosaeta while only containing EAC didn't function significantly. On the contrary, potential H2 -competitors (e.g. Hydrogenophaga ) of methanogens could also clone onto biochar that may weaken its DIET benefit for methanogenesis, which was observed in high throughout sequencing. Meanwhile, suspended microbes, which cannot conduct DIET with biochar, were far more extensive than those attached to additives, indicating that biochar also affects microbial activity through other surrounding biochemical connections. The identification of limited application scope of biochar and numerous suspended microbes provides new considerations into the mechanisms of surrounding limitation for biochar application and possible determinants except for DIET. Graphical abstract: Image 1 Highlights: The promotional effect of biochar on microbes was limited to stressed scenarios. EDC plays a vital role in the promotional function of biochar. Biochar has a selectivity of enriching Methanosaeta and Methanosarcina. There could exist other pathways beyond DIET for biochar affecting microbes.